HIDRASI IKATAN RANGKAP C7-8 SENYAWA KALANON DAN UJI SITOTOKSISITASNYA TERHADAP SEL LEUKEMIA L1210 - Mochamad Chasani; Eva Vaulina; Ponco Iswanto; Yayu Rahayu (Molekul, 2010)
Calanone is anticancer compound that is isolated from species Calophyllum. The biological activity of calanone againts leukemia cell L1210 is relatively low showed by IC50 value at 59.4 μg/mL. A compound have a high biological activity if the value of IC50 under 10 μg/mL. This research aimed to obtained calanone hydrat compound which has a higher activity to inhibit leukemia L1210 cancer cell growth. Calanone hydrat compound is got through with two step reaction, first step was protonated double bond by acetic acid reagent and the second step is nucleophilic addition by water. Initial analysis for the synthesize product compound is done with thin layer chromatography (TLC) using n-hexane and ethyl acetate 2:1 (v/v) eluent. Coloum Chomatography and recrystallization is used to pure the synthesize product compound with n-hexane and methylen chloride 1:1 (v/v) solvent. The result analyzed by thin layer chromatography. The synthesized product give Rf at 0.4545 and rendement 4.72% (w/w), forming of brownish yellow chromatic powder and melting point at 190oC-192oC. Identification structure of synthesize product compound is done with mass spectrometer. The result of mass spectrometer identification were moleculer ion M+-18 (M+ 424) with fragments m/e=409, m/e=395, m/e=381, m/e= 331, m/e=317, m/e=303, me/=176, m/e=105, and m/e=77. Citotoxicity test againts leukemia cell L1210 yield the value IC50 equal to 45.64 μg/mL.